Problematika Quick Response Peserta Didik pada Mata Pelajaran PAI Kelas XI di SMAN 1 2X11 Enam Lingkung - Rani Salsabila; Rahmi Wiza (Lembaga Yasin AlSys, 2026)
Although the issue of students’ quick response in Islamic Education (PAI) learning has received attention in various studies, research that specifically positions this phenomenon as a form of multidimensional student engagement remains limited. This study aims to describe the problems of students’ quick response, analyze the supporting and inhibiting factors, and identify teachers’ efforts to improve it. This study employed a qualitative approach with a descriptive qualitative design, involving 13 participants consisting of school personnel, teachers, and eleventh-grade students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using the interactive analysis of Miles and Huberman. The results showed that the problems of students’ quick response were characterized by slow responses, low participation, passive tendencies, and hesitation in answering. The supporting factors included interactive learning methods, engaging learning media, a conducive classroom atmosphere, and teacher motivation, whereas the inhibiting factors included low self-confidence, lack of understanding of the material, less varied methods, and a less supportive learning environment. These findings contribute to strengthening the concept of student engagement in Islamic Education (PAI) learning. This study concludes that improving students’ quick response requires interactive and innovative learning strategies, and also confirms the importance of optimizing active learning methods and utilizing digital media to improve learning quality.